The intermediary mechanism of social fairness perceptions between social capital and farmers’ political participation: Empirical research based on masking and mediating effects - Hou, Bo; Liu, Qiang; Wang, Zhiwei; Hou, Jing; Chen, Suyun (Frontiers in Psychology, 2023)
Political scientists have conducted extensive research on the factors influencing political participation, but empirical analyses examining them from the perspective of social fairness perceptions are not common. Using large-scale data from the Chinese General Social Survey (CGSS), this study explores the intermediate mechanisms of social fairness perceptions in the influential relationship between social capital and farmers’ diversified political participation. The results show that the positive relationship between social capital and farmers’ political behavior is indirectly influenced by different dimensions of the sense of social fairness. Among them, social trust and social network variables affect political participation mainly through the mediating role of outcome fairness perceptions, while opportunity fairness perceptions significantly widen the gap in political participation between low and high social trust. Therefore, the government should nurture the social capital of rural geo-relational networks and formulate policies based on a social justice perspective in order to enhance rural residents’ outcome fairness perceptions and increase the political participation of farmers.